A Pilot Evaluation of a Mindful Self-care and Resiliency (MSCR) Intervention for Nurses - Craigie, Mark; Slatyer, Susan; Hegney, D.; Osseiran-Moisson, R.; Gentry, E.; Davis, S.; Dolan, T.; Rees, Clare (2016)
It is now well established that a significant number of nurses have less than optimal levels of wellness as a result of the stressful nature of their work. Identifying effective workplace strategies to help improve the resilience of nurses is therefore a high priority. In this study, we evaluated the feasibility of a mindfulness-based intervention aimed at reducing compassion fatigue and improving emotional well-being in nurses. A total of 21 nurses recruited from a large teaching hospital in Western Australia, participated in a mindful self-care and resiliency (MSCR) intervention. The intervention consisted of a 1-day compassion fatigue prevention educational workshop, followed by a series of weekly mindfulness training seminars conducted over 4 weeks (12 h total intervention time). Participants completed a number of standardized measures at pre, post, and 1-month follow-up. Significant improvements were observed following the intervention for compassion satisfaction, burnout, trait-negative affect, obsessive passion, and stress scores.At pre-intervention, 45 % of the sample had high burnout scores, but this reduced to just 15 % by post-intervention. No significant changes were observed for general resilience, anxiety, or secondary traumatic stress post-intervention or at follow-up. The results of this preliminary study indicate that MSCR may represent a feasible approach to improving resilience and well-being among nurses. Further research utilizing a control group is required to strengthen conclusions